2018
DOI: 10.3390/agriculture9010004
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Irrigation Schedules as a Strategy to Mitigate Climate Change Impacts on Agriculture in Cyprus

Abstract: The study aimed at investigating eventual deviations from typical recommendations of irrigation water application to crops in Cyprus given the undeniable changes in recent weather conditions. It focused on the seasonal or monthly changes in crop evapotranspiration (ETc) and net irrigation requirements (NIR) of a number of permanent and annual crops over two consecutive overlapping periods (1976-2000 and 1990-2014). While the differences in the seasonal ETc and NIR estimates were not statistically significant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The window size and degree of the polynomial were 12 and 2, respectively [18]. The MSC eliminated the spectral differences caused by different scattering levels, enhancing the correlation between spectra and data [19]. However, SNV eliminated the influence of solid particle differences and information about the measured substances [20].…”
Section: Spectral Preprocessingmentioning
confidence: 99%
“…The window size and degree of the polynomial were 12 and 2, respectively [18]. The MSC eliminated the spectral differences caused by different scattering levels, enhancing the correlation between spectra and data [19]. However, SNV eliminated the influence of solid particle differences and information about the measured substances [20].…”
Section: Spectral Preprocessingmentioning
confidence: 99%
“…For example, in arid and semi-arid regions, irrigated open-field crops are usually cultivated from March to September, in most cases under completely clear sky conditions. The total irrigation requirements for the main crops may rise from 350 (e.g., vegetables) to 2400 (e.g., colocasia) mm (i.e., 3500–24000 cubic meters of water per hectare) (Dalias et al 2019 ; Nikolaou et al 2020a , b ). Because crops in these areas depend on sufficient supplies of high-quality water, the availability of water has always been an issue (Sánchez-Molina et al 2015 ; Nikolaou et al 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Drought is one of the major abiotic stresses that cause significant reductions in crop yield and quality [1,2] and is expected to be more severe since the occurrence of drought is increased due to alteration in the evapotranspiration (ET) as well as unfavorable rainfall distribution caused by global warming [3,4]. Several study results have shown that the negative consequences of drought can be overcome by adaptation of different strategies to improve the climate resilience of agriculture, i.e., sowing time [5][6][7], tillage systems [8,9], irrigation [10][11][12], selection of crop and varieties [13,14] and use of beneficial soil bacteria and mycorrhizal fungi [15,16]. The latter was reported in the literature as a complementary measure that can mitigate the effects of biotic and abiotic stresses in crop production [16].…”
Section: Introductionmentioning
confidence: 99%